Swearing and how to deal with it in the classroom - Fiona Elizabeth Oliver (2011)
Swearing is a phenomenon that has been overlooked in EFL/ESL classrooms in Iceland and little has been published on the subject. EFL teachers should help pupils learn the use of appropriate language in the appropriate context. This study aimed to investigate teachers’ attitudes and approaches to teaching about swearing and appropriate language use in EFL classrooms in Iceland. In this research paper I examined the sociolinguistics of swearing by discussing taboo language, recalling taboo language and exploring the relationship between language and culture. Key words: Swearing, appropriate language, taboo, culture, EFL.